Decline of ectomycorrhizal fungi following a mountain pine beetle epidemic. Issue 4 (1st April 2014) - Treu, Roland; Karst, Justine; Randall, Morgan; Pec, Gregory J.; Cigan, Paul W.; Simard, Suzanne W.; Cooke, Janice E. K.; Erbilgin, Nadir; Cahill, James F.
Abstract : Forest die‐off caused by mountain pine beetle (MPB; Dendroctonus ponderosa ) is rapidly transforming western North American landscapes. The rapid and widespread death of lodgepole pine ( Pinus contorta ) will likely have cascading effects on biodiversity. One group particularly prone to such declines associated with MPB are ectomycorrhizal fungi, symbiotic organisms that can depend on pine for their survival, and are critical for stand regeneration. We evaluated the indirect effects of MPB on above‐ (community composition of epigeous sporocarps) and belowground (hyphal abundance) occurrences of ectomycorrhizal fungi across 11 forest stands. Along a gradient of mortality (0–82% pine killed), macromycete community composition changed; this shift was driven by a decrease in the species richness of ectomycorrhizal fungi. Both the proportion of species that were ectomycorrhizal and hyphal length in the soil declined with increased MPB‐caused pine mortality; <10% of sporocarp species were ectomycorrhizal in stands with high pine mortality compared with >70% in stands without MPB attacks. The rapid range expansion of a native insect results not only in the widespread mortality of an ecologically and economically important pine species, but the effect of MPB may also be exacerbated by the concomitant decline of fungi crucial for recovery of these forests.